Dynamics of Gen-Z Students' Thinking in the Contemporary Era - Pratiwi Amalia Putri Tiwi; Mahdi Hidayatullah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
This research examines how Generation Z students at the Darunna'im Pontianak Islamic Boarding School face the challenges of the contemporary era marked by the advancement of digital technology and rapid social change. Using a qualitative approach with a case study method, data was collected through in-depth interviews with students and caregivers of Islamic boarding schools and observation of students' daily activities. The study results show that Generation Z students are open to digital technology, especially social media, to integrate religious teachings with modern life. Despite the challenges of balancing Islamic values with the demands of modernity, such as technology-based education and gender equality, students still maintain their Islamic identity. This study concludes that Gen-Z students at the Darunna'im Islamic Boarding School have successfully demonstrated critical adaptability to globalization while maintaining traditional Islamic values.